Behavior change communication campaign on awareness and prevention of zoonoses, designed for health workers to deliver to patients - CGIAR Research Program on Agriculture for Nutrition and Health (2018)
The public health campaign/materials developed and disseminated as part of a CGIAR research project are being used in public sector hospitals in Kenya. The link is to a 2017 publication. Materials used in the campaigns can be provided upon request.